Analysing the Role of English Language Proficiency (TOEFL) in Increasing Job Opportunities in the Global Industry Sector - Khoiruman, Muhamad Alfi; Irawan, Doni Hadi (Huele: Journal of Applied Linguistics, Literature and Culture, 2025)
This study aims to explore the role of English language proficiency, particularly TOEFL scores, in enhancing employment opportunities in the global industrial sector. Globalisation has driven major changes in the way companies operate, and English is now an international language used not only in everyday communication but also in business transactions, negotiations, and strategic decision-making. Along with this development, mastery of English has become one of the main requirements in the recruitment process of many international companies, especially those with operations in various countries. In the global industrial sector, multinational companies look for employees who can communicate well in English as they interact with various parties from different parts of the world. Therefore, good English proficiency, as measured through TOEFL scores, is considered an indicator of an individual's ability to adapt and work effectively in a multinational work environment. This study uses a qualitative approach with in-depth interviews with 25 professionals working in multinational companies operating in various industry sectors, such as technology, finance, and manufacturing. The results show that TOEFL scores are not only used as a parameter in job selection, but also as an important indicator in the assessment of communication skills required in cross-national and cultural interactions. Respondents revealed that a good command of English, as evidenced by a high TOEFL score, opens up more career opportunities, including the chance to get higher positions, greater responsibility, and more competitive salaries. Therefore, this study provides recommendations for individuals to further emphasise mastery of English through the TOEFL test as an effort to increase competitiveness in the global job market, as well as for educational institutions and companies to make more use of TOEFL scores in assessing the qualifications of prospective employees.